"cART intensification by the HIV-1 Tat B clade vaccine: progress to phase III efficacy studies". (1st February 2018) - Cafaro, Aurelio; Sgadari, Cecilia; Picconi, Orietta; Tripiciano, Antonella; Moretti, Sonia; Francavilla, Vittorio; Pavone Cossut, Maria Rosaria; Buttò, Stefano; Cozzone, Giovanni; Ensoli, Fabrizio; Monini, Paolo; Ensoli, Barbara
ABSTRACT: Introduction : In spite of its success at suppressing HIV replication, combination antiretroviral therapy (cART) only partially reduces immune dysregulation and loss of immune functions. These cART-unmet needs appear to be due to persistent virus replication and cell-to-cell transmission in reservoirs, and are causes of increased patients' morbidity and mortality. Up to now, therapeutic interventions aimed at cART-intensification by attacking the virus reservoir have failed. Areas covered : We briefly review the rationale and clinical development of Tat therapeutic vaccine in cART-treated subjects in Italy and South Africa (SA). Vaccination with clade-B Tat induced cross-clade neutralizing antibodies, immune restoration, including CD4 + T cell increase particularly in low immunological responders, and reduction of proviral DNA. Phase III efficacy trials in SA are planned both in adult and pediatric populations. Expert commentary : We propose the Tat therapeutic vaccine as a pathogenesis-driven intervention that effectively intensifies cART and may lead to a functional cure and provide new perspectives for prevention and virus eradication strategies.